Nasionalisme Papua Dalam Organisasi Aliansi Mahasiswa Papua (Studi Kasus : Aliansi Mahasiswa Papua Komite Kota Yogyakarta) - Alam Maha Dika (Jurnal DinamikA, 2020)
The Papuan Student Alliance (AMP) is a Papuan student organization that voices problems in Papua, especially politics. AMP has goals for Papuan independence which are contained in the organization's vision and platform. AMP itself is divided into seven committees in various cities, one of which is the Yogyakarta City Committee. The results of this study conclude that the Papuan nationalism that has developed within the Yogyakarta KK AMP is due to several reasons, among others; 1) Indonesia is considered a failure in carrying out nation-building in Papua; 2) Experience of violence experienced by the Papuan people; 3) The basic needs of the Papuan people are not fulfilled. Apart from the historical factor of Papua which has a strong connection with Papuan nationalism, the failure of nation-building by Indonesia in Papua is also a factor that makes Papuan nationalism continue to develop in the Yogyakarta KK AMP. In the construction of Papuan nationalism, the Yogyakarta KK AMP builds a shared identity through shared psychology regarding the oppression experienced by the Papuan people so far. The joint history that was formed by the AMP KK Yogyakarta is about Papua which has made efforts to become independent and then this independence was annexed by Indonesia. For the AMP KK Yogyakarta, the Papuan people have experienced violence (memoria passionis), land grabbing, exploitation of natural resources, discrimination, marginalization, and the crisis of freedom. Therefore, the common goal of AMP KK Yogyakata is Papuan independence as an initial stage towards a better Papua.